2016
DOI: 10.1186/s40064-016-2948-0
|View full text |Cite
|
Sign up to set email alerts
|

Ex-vivo evaluation of the mucoadhesive properties of Cedrela odorata and Khaya senegalensis gums with possible applications for veterinary vaccine delivery

Abstract: BackgroundFew studies have investigated the interaction of bioadhesives with biologic tissues for veterinary application. Hence, this study evaluates the mucoadhesive property and vaccine delivery properties of polymers from phytogenic origin. Gums from Cedrela odorata and Khaya senegalensis were harvested, purified, dried and compressed into 500 mg tablets individually and in combined ratios. The time taken for these tablets, placed on freshly excised (5 × 5 cm) trachea and duodenal tissues of cattle, chicken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
(23 reference statements)
2
4
0
Order By: Relevance
“…Generally, the observed reduction in clinico-pathological features observed in the gum-vaccine groups might be related to the humoral systemic and mucosal responses to previous booster vaccination as suggested and demonstrated in our previous studies [13] , [14] . These studies showed a higher and faster peak humoral (mucosal and systemic) response (using HI and ELISA) [14] in challenged chickens after prior and booster oral NDV vaccinations when gum vehicle was employed.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Generally, the observed reduction in clinico-pathological features observed in the gum-vaccine groups might be related to the humoral systemic and mucosal responses to previous booster vaccination as suggested and demonstrated in our previous studies [13] , [14] . These studies showed a higher and faster peak humoral (mucosal and systemic) response (using HI and ELISA) [14] in challenged chickens after prior and booster oral NDV vaccinations when gum vehicle was employed.…”
Section: Discussionsupporting
confidence: 67%
“…This study was aimed at evaluating the clinicopathologic features of challenged chickens previously vaccinated with ND vaccine using natural mucoadhesive biopolymers such as gums from plants. This was following recent reports by Emikpe et al [13] who reported strong mucoadhesive property of gums obtained from Cedrela odorata and Khaya senegalensis trees when used as vaccine vehicles with a suspected immunopotentiating action when investigated using ex-vivo means. Further, Oyebanji et al [14] reported higher, faster serum and mucosal humoral responses in an in vivo model with challenged chickens previously vaccinated against Newcastle disease using these gums as delivery vehicle.…”
Section: Introductionsupporting
confidence: 82%
“…Next to the ability of mucosa in covering the nasal cavity, the applied drug/vaccine can be directly transferred to the systemic blood circulation without facing the hepatic first pass effect and intestinal metabolism. However, oral vaccines can provide certain advantages such as simple usage, low cost, and mucosal immune responses (Smart et al 1984 ; Peppas and Sahlin 1996 ; Emikpe et al 2016 ; Yonesi and Kamrani 2019 ). In addition, natural gums proved to be an appropriate choice for delaying the drug release, which has led to the growing interest in the application of these polymers in sustained drug and vaccine delivery (Bhosale et al 2014 ; Manjula et al 2014 ; Cox et al 1999 ).…”
Section: Use Boswellia Species In Vaccine Formulat...mentioning
confidence: 99%
“…It is then allowed to pass through sieve (0.15-mm mesh size). The isolated AH gum powder was packed properly and stored in desiccators [18].…”
Section: Isolation Of Ah Gummentioning
confidence: 99%